Passidakka: Pemberian Sedekah Bagi Orang Meninggal Di Jeneponto - Nita Puspita Sari; Mubarak Dahlan (Rayhan Intermedia, 2023)
This study aims to find out the views of village priests regarding passidakka beliefs in Gantarang Village, Kelara District, Jeneponto Regency, the meaning of passidakka for the community, and changes in passidakka culture. This type of research is descriptive qualitative. Collection is done through observation, interviews and documentation. The technique of determining informants by purposive sampling with predetermined criteria. Data analysis techniques are qualitative and for data validation techniques use source triangulation techniques. The results of the study show that: (1) The village priest strongly supports this passidakka ritual as long as it meets the existing criteria, namely it is carried out sincerely and without exaggeration so that this ritual can achieve its goals without causing pride to those who carry it out and envy to those who witness it ; (2) The passidakka ritual has become part of the people of Gantarang Village, that is, with the passidakka they hope that their departed family can get a proper place for it, on the one hand passidakka is also a cultural heritage that needs to be preserved; (3) In practice, passidakka has changed. Previously, the objects that were donated were only simple objects left by people who had died, such as trays, cups, clothes, plates and so on. Now it has turned into luxurious, expensive and all-new things, such as spring beds, wardrobes, sofas, mattresses, bolsters, head pillows, plates, glasses, cups, trays and so on.